Health Information Systems Technological and Management Perspectives - Winter, Alfred (Health Informatics, 2023)
This heavily revised open access edition provides a thorough overview of the technologies available to assemble, manage and assess the quality of health information systems. It details a variety of scenarios in the context of both health and heath care, including where prevention and wellness are related, such as the treatment of both acute and chronic diseases. Stakeholder requirements are also described to provide perspectives for describing the architectures and management techniques associated with health information systems, enabling the reader to develop a detailed holistic overview of the subject. Health Information Systems: Technological and Management Perspectives features a detailed overview of how information systems in health care can be managed and is a vital resource for medical informatics students seeking an up-to-date text on the topic.